Policy Framing and Party Competition: The Italian Political Debate on Local Public Services since the Economic Crisis - Tarditi, Valeria (PARTECIPAZIONE E CONFLITTO, 2020)
In recent years many European governments reacted to the economic crisis introducing austerity measures that particularly affected Local Public Services (LPSs) through outsourcing, privatization and marketization. While several studies have analysed the logics of instruments choice also in this policy sector, the political discourses and policy frames that accompanied the tools selection for the management of LPSs in the last years have been paid limited attention in the scholarly literature. Starting from these premises, the article analyses the debate on LPSs that has developed in Italy since 2008, reconstructing the frames used by the main parties through the analysis of both electoral manifestos and press reviews of articles relevant to LPSs in three newspapers. Particular attention is paid to the 2011 referendum against the privatization of LPSs and the 2018 referendum on local public transportation management in Rome. The paper concludes that the economic crisis and subsequent transformations of party politics and participation encouraged a politicization of the issues around local public services, as well as a shift in the related policy discourse. The parties' choices and policy frames were guided mainly by a strategic logic defined in relation to the salience of the LPS issue and the competitive context.